2017
DOI: 10.1016/j.healun.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular and pulmonary vascular reserve in asymptomatic BMPR2 mutation carriers

Abstract: The presence of a BMPR2 mutation, per se, is not associated with an abnormal pulmonary vascular and right ventricular functional response to exercise in asymptomatic individuals. Longer follow-up will be required to determine whether a P/Q slope of >3 mm Hg/liter/min during exercise in normoxia or hypoxia is a sign of pre-clinical disease expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Many factors downregulate BMPR2 signaling and receptor expression outside of germ line and somatic mutations. As BMPR2 haploinsufficiency in patients alone is not sufficient to alter pulmonary vascular resistance or RV functional reserve [ 147 ], what genes or factors either provide the second hit, or reduce BMPR2 signaling to the level required to become pathogenic? As outlined, a BMPR2-deficient immune system may have the potential to develop auto-reactivity and act as the second hit.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors downregulate BMPR2 signaling and receptor expression outside of germ line and somatic mutations. As BMPR2 haploinsufficiency in patients alone is not sufficient to alter pulmonary vascular resistance or RV functional reserve [ 147 ], what genes or factors either provide the second hit, or reduce BMPR2 signaling to the level required to become pathogenic? As outlined, a BMPR2-deficient immune system may have the potential to develop auto-reactivity and act as the second hit.…”
Section: Discussionmentioning
confidence: 99%
“…After administration of intravenous sildenafil, the second exercise challenge resulted in a different pulmonary hemodynamic response with lower maximal mPAP, PVR, and TPR, a more shallow mPAP/CO slope, and increases in PAC and CO. Measures of RV steady (PVR) and pulsatile (PAC) afterload [ 40 ], pulmonary vascular reserve (TPR) [ 41 ], and RV backward failure (RAP) showed improvement due to an acute unloading. However, aside from RAP, any of these calculated parameters depend on CO and therefore cannot be interpreted in the absence of RV contractility.…”
Section: Discussionmentioning
confidence: 99%
“…61 Even in asymptomatic individuals with bone morphogenetic protein receptor type 2 mutations but no overt clinical manifestations, exercise cardiovascular MRI can help uncover abnormal pulmonary vascular function not evident at rest. 46 Interestingly, healthy controls have been found to have a blunted capacity for augmentation of RV systolic function when exposed to hypoxia during exercise, although not to the same degree as patients with pulmonary hypertension under normoxic conditions. 49 In addition to patients with repaired tetralogy of Fallot discussed previously, Barber et al demonstrated the feasibility of coupling cardiovascular cardiac MRI with CPET in patients with pulmonary arterial hypertension, who were found to experience significant worsening of ventricular septal curvature during exercise and impaired peak tissue oxygen extraction capacity.…”
Section: Coronary Artery Disease (Known or Suspected)mentioning
confidence: 99%
“…In a subset of patients with relatively low‐risk pulmonary arterial hypertension, exercise cardiovascular MRI has shown the ability to stratify patients into those who can or cannot augment RV SV during exercise 61 . Even in asymptomatic individuals with bone morphogenetic protein receptor type 2 mutations but no overt clinical manifestations, exercise cardiovascular MRI can help uncover abnormal pulmonary vascular function not evident at rest 46 …”
Section: Use In Clinical Populationsmentioning
confidence: 99%
See 1 more Smart Citation